How Common Is Commercial Contract Cheating in Higher Education and Is It Increasing? A Systematic Review - Newton, Philip M. (Frontiers in Education, 2018)
Contract cheating, where students use a third party to complete their assignments, is frequently reported to be increasing, presenting a threat to academic standards and quality. Many incidents involve payment of the third party, giving contract cheating a commercial aspect. This study synthesised findings from prior research to try and understand how common self-report of contract cheating is in Higher Education, and test whether it is increasing. It also sought to evaluate the quality of the research evidence which addresses those questions. 71 samples were identified from 65 studies, going back to 1978. These included 54514 participants. Contract cheating was self-reported by a historic average of 3.52 % of students, with evidence that this has increased in recent years; a positive relationship was found between time and the percentage of students admitting to contract cheating, and in samples from 2014 to present the figure is 15.7%, representing approximately 31 million students around the world. This increase may be due to an overall increase in self-reported cheating, rather than contract cheating specifically. Most samples were collected using designs which makes it likely that contract cheating is under-reported, for example using convenience sampling, with a very low response rate and without guarantees of anonymity for participants. Recommendations are made for future studies on academic integrity and contract cheating specifically.